Atypical presentation of pilomatrixoma in the tarsal conjunctiva - Dittrich,Mirtha Ramirez (2016)
ABSTRACT Pilomatrixoma is a rare benign tumor, which usually affects young women in the head and neck region. The eyelid is a common site of the disease, though it is very rare in the tarsal conjunctiva.The pilomatrixoma has clinical pleomorphism, which confuses this disease with other similar conditions. The diagnosis is made by pathological examination in most cases. The treatment is surgical, performed by total excision of the lesion with clear margins and recurrence is very uncommon.We present an unusual case of probable recurrent pilomatrixoma in the left upper tarsal conjunctiva.